DEVELOPING STUDENTS’ READING SKILL THROUGH MAKING MULTIMODAL INFERENCES - Vina Nurviyani; Didi Suherdi; Iwa Lukmana (English Review: Journal of English Education, 2020)
This present study investigated the development of students’ reading skills through making multimodal inferences. Moreover, the students’ difficulties in making multimodal inferences were explored. This study applied a classroom action research by involving twenty students studying at English education program in West Java. Three instruments covering reading tests of making multimodal inference, classroom observations, and questionnaire were conducted as data collections of this study. The results of this study indicate that the students’ reading skills improved significantly after making multimodal inferences. In the first cycle, sixty three percent of all students achieved the score more than seventy. Meanwhile, in the second cycle, eighty five percent of all students reached the score more than eighty-seven. It is reflected on the data gained from reading tests, classroom observations, and questionnaire. The findings show that almost all students achieved meaningful progress of reading skills through making multimodal inferences that they were able tomake inferences visually and verbally by using the clues of the texts and integrating it with their background knowledge, creating mental images in their minds, distinguishing between literal and implied meanings, implementing some reading strategies before, during, and after reading the text, and manifesting their inferences visually and verbally on Canva application. Thus, they were able to master micro and macro skills of reading comprehension and comprehend the multimodal texts completely.However, in making multimodal inference, some students got troubles in integrating visual and verbal aspects because of incomplete background knowledge in their minds. Therefore, the manifestation of their multimodal inferences was presented partially.